MEKANISME AKSI DAN EFIKASI OBAT-OBATAN BOTANI YANG BERPOTENSI DALAM PENGOBATAN ALTERNATIF UNTUK FIBROID UTERUS - Tiara Sekar; Rodiani; DWi Aulia Ramdini (CV. Jasa Sukses Abadi, 2022)
Uterine fibroids are benign gynecologic tumors that develop from the myometrium and become entangled in the majority of women. The available pharmacological treatments are useful for reducing the size of the fibroids and relieving the symptoms of uterine fibroids. However, these pharmacological agents are said to be unaffordable for most people and are also associated with considerable side effects. Therefore, botanical medicines stole the attention in the last decade because of their therapeutic effectiveness accompanied by affordable costs and comparable and stronger therapeutic efficacy, with fewer side effects. The aim of this review is to provide information regarding the mechanisms by which various botanical drugs possess uterine anti-fibroid activity. The source search method is carried out through several trusted websites such as Pubmed, Science Direct, and Google Scholar. Based on the literature that has been identified, five botanical drugs were found which will be discussed in this review. These botanical drugs will be explained their mechanism of action in carrying out uterine anti-fibroid activity which has the potential as an alternative treatment for uterine fibroids.